Implementation of a Deep Learning Approach in Akidah Akhlak Instruction to Strengthen Students’ Reflective Thinking Skills - Mohammad Ariswara Rai Djafar; Lukman Arsyad; Burhanudin Abdul Karim Mantau (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2026)
This study aims to analyze the implementation of the Deep Learning approach in Akidah Akhlak instruction at MTs Negeri 1 Banggai in order to strengthen students’ reflective thinking skills. This effort responds to the limitations of conventional instruction, which has tended to be normative and memorization-oriented, with the expectation that learning can become more meaningful and contextual.The research employed a qualitative method with a case study design. Data were collected through classroom observations, in-depth interviews with teachers, students, the principal, and parents, as well as documentation of instructional materials. Data were analyzed using an interactive model involving data condensation, data display, and conclusion drawing. The findings indicate that the implementation of Deep Learning occurs through contextual lesson planning, dialogic classroom practices, the use of moral cases closely related to students’ everyday lives, and assessment practices that emphasize students’ ability to reflect on values of faith. The conclusion of this study confirms that the Deep Learning approach is effective in strengthening students’ reflective thinking skills, as students are not only able to understand content at a textual level, but also evaluate behavior, consider moral consequences, and develop self-awareness based on Islamic teachings.